The role of English in medicine - Nuriddinov Abdulmuiz Nuriddin o`g`li; Nuraliyeva Ozoda Norbayevna; Tolibova Vazira Timurovna; Sobirjonova Marjona Jamshedovna (Genius Publishing Group, 2022)
The English language is becoming not only a means of international communication, but also a common human language in various fields and also in medicine.If we talk about the field of medicine, it is difficult to build a career in English without knowledge of speech patterns, medical terminology and stable phrases. Knowledge of English language enables us to participate in various international medical conferences, after which we can cooperate with international colleagues in the field of health care. The main purpose of learning a foreign language in medical schools is the practical use of the foreign language as a professional communication, information activities and further self-education.
Keywords: English; conference; terminology; exchange of experiences